Splenic artery use for arterial reconstruction in pancreatic surgery - Hackert, Thilo; Weitz, Jürgen; Büchler, Markus W. (Langenbeck's archives of surgery, 2014)
Extended resections in the upper GI tract, especially for pancreatic malignancies, can require resection of the hepatic or superior mesenteric artery. Besides venous or allogenous grafting, the splenic artery can be used for reconstruction in both positions.